Material culture of Scottish reform politics, 1820-1884 - Angus, Sonny (The University of Edinburgh, 2022)
Material culture is an underused source base for the analysis of nineteenth-century mass politics. While much has been written on the speeches of political leaders, the arguments on newspaper pages, and the memoirs of radicals, the materials used by those who made up the century’s movements for reform are rarely analysed. Such written sources are no doubt useful, providing as they do an insight into the ideologies which drove mass movements. However, when used alone they paint an incomplete picture. A more complete picture of what drove rank-and-file radicals to engage in franchise reform can be reached by including an attention to the material cultures of these movements. Work has been done to this effect on the actions of political crowds in the first half of the century. However, very little of this research focusses on the materials wielded by those present. Thus, a more object-focussed study is necessary to fully draw out the usefulness of material culture as a source base. This thesis attempts to develop a fuller understanding of nineteenth-century reform movements by engaging with material culture in two key ways. First, it attempts to understand what form the materials took and how they were used, then it applies these findings to broader questions on the nature of nineteenth-century reform movements. To this end, the first chapter examines the use of political objects in the home. In doing so, it outlines how reformers infused politics within their creations of domestic space. It then looks at those objects used in the public sphere, aiming to understand how and why radicals turned out in the organised processions analysed throughout the thesis. With the ‘how’ and ‘what’ of radical material culture established, the thesis then turns its attention to understanding how materials can be used to analyse these movements. The following two chapters, then, focus on two core elements of radical identity: class and gender. Class was a central identity within reform movements and the third chapter examines how radicals’ use of materials reflected and reinforced their class identities. Specifically, it looks to address questions which have long been a focus of historiography: how was class conceptualised and what ties did it have with radicalism? Gender was also central to reform movements and deeply tied to class identities. As such, material culture is examined in the fourth chapter for what it can tell us about the changing gendered roles of men and women in these movements through the century. Finally, the radicals’ use of monuments in commemorating their struggles and the struggles of others will be examined, so as to show how history-making played a role in the construction and maintenance of political identity. Overall, this thesis will show the utility of including material culture as a source base for our understanding of nineteenth-century franchise reform movements and broaden our understanding of these movements in the process.
The material culture of Scottish reform politics, 1820-1884
Keywords: n/a